VARIABILITY IN RIGHTS ENFORCEMENT: A COMPARATIVE PERSPECTIVE - Whitehead, Laurence (Revista Debates, 2008)
The article looks at a partial selection of the many rights claimed by citizens in contemporary democracies in the context of the justice system, citizen security, gender, youths, and access to information – and presents the argument that that democratic “rights” are not a homogeneous reality as posited by liberal theory, but a complex, multilayered one. In new “low quality” democracies, rights volatility presents a special challenge to universality. Social mapping of the range and distribution of bankable rights is likely to uncover a reality that falls well short of the rhetoric of universalism. In highly fragmented and unequal societies, the rhetoric of universality is unlikely to translate easily into genuine evenness of application. And accompanying variability there may be instability or volatility over time. This combination in societies where the “duties” corresponding to rights are not securely internalised, is liable to produce patterns of political behaviour that deviate substantially from the interlocking mutuality of interest postulated by classical liberalism. “Contentious” political cycles of resistance and exclusion, and struggles to reshape the rules of the game (rather than merely to live within them) seem to be natural correlates of this climate of uncertainty. This is particularly so in new democracies, where sudden explosions of rights claims and multiplying rights claimants can easily generate an atmosphere of rights inflation can raise expectations well beyond what is reliably deliverable.